Quality of Life and the Millennium Challenge
IX, 282 p.
Keywords: The new millennium is widely considered to be the age of globalisation, democratisation, and human rights. We live in a knowledge society and in a time of risk and uncertainty. World society is rapidly urbanising and ageing and exhausting its natural resources. It is the interplay of such key trends of the era that calls for a fresh approach to measuring quality of life. This collection of papers presents an innovative approach to evaluating living standards and wellbeing under the new circumstances facing individuals and societies in twenty-first century. Contributions cover a wide range of issues that impact positively and negatively on wellbeing in our age. While stability, trust, equal access to resources and the social integration of disadvantaged members of society enhance well-being, poverty, social exclusion, congestion in cities, HIV/AIDS and global warming pose threats to both modern and traditional lifestyles. Methodological refinements of conventional measurement tools are presented that take into consideration the rich diversity of lifestyles and values among different populations and regions of the world. This book will be essential reading for social scientists and ordinary citizens who are concerned about the future of human well-being on our planet.